2014
DOI: 10.1890/13-1269.1
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater availability and coastal wetland foundation species: ecological transitions along a rainfall gradient

Abstract: Climate gradient-focused ecological research can provide a foundation for better understanding critical ecological transition points and nonlinear climate-ecological relationships, which is information that can be used to better understand, predict, and manage ecological responses to climate change. In this study, we examined the influence of freshwater availability upon the coverage of foundation plant species in coastal wetlands along a northwestern Gulf of Mexico rainfall gradient. Our research addresses th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 59 publications
2
98
0
Order By: Relevance
“…Recent studies have shown that changes in macro-climate drivers, such as precipitation and temperature, have the potential to impact coverage of foundation species in coastal wetlands (Osland et al 2016). Drier conditions are predicted to cause declines in foundation species coverage (Osland et al 2014), and our findings underscore the need for a better understanding of how ecological function at the landscape scale will be impacted by changes in macroclimate drivers.…”
Section: Discussionmentioning
confidence: 59%
“…Recent studies have shown that changes in macro-climate drivers, such as precipitation and temperature, have the potential to impact coverage of foundation species in coastal wetlands (Osland et al 2016). Drier conditions are predicted to cause declines in foundation species coverage (Osland et al 2014), and our findings underscore the need for a better understanding of how ecological function at the landscape scale will be impacted by changes in macroclimate drivers.…”
Section: Discussionmentioning
confidence: 59%
“…Targeted field and greenhouse-based experiments are needed to refine our understanding of mangrove freeze damage and mortality thresholds. There is a need for the identification of species-specific thresholds (Cavanaugh et al 2015;Lovelock et al, in press) and for a better understanding of the physiological effects of interactions between low temperatures and other stressors including freshwater limitation and high salinity (Osland et al 2014b). Our research has not directly quantified the relationships between specific temperature regimes and mangrove life stage-dependent damage and recovery, but rather the response of different mangrove life stages to environmental conditions associated with low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…; Osland et al . ; Osland, Enwright & Stagg ). In tidal saline wetlands, foundation plant species (sensu Dayton ; Ellison et al .…”
Section: Discussionmentioning
confidence: 99%